Megjegyzések a honfoglalás kori (öv)veretek kutatásának helyzetéről kiválasztott problémák - Bollók Ádám (2013)
The present paper is based on the results of the authors MA thesis defended in 2007 as well as of supplementary researches conducted for various projects thereafter. Belt mounts undoubtedly represent one of the most characteristic groups of Ancient Hungarian material culture recovered from tenth-century grave assemblages. Until 2007 some 247 units (from single stray finds of unknown provenance to properly excavated and documented grave and settlement finds) were registered. However, since one particular type of tenth-century horse harnesses has been likewise decorated with mounts identical or highly similar in shape and ornamentation to the belt appliqués, it is almost certain that the 247 catalogued units do not indicate 247 former belt sets. Given that previous attempts at separating mounts decorating belts and horse harnesses on purely typological grounds remained inconclusive, in the authors judgement it seems appropriate to introduce a new label and to speak about (belt) mounts when denoting non-ferrous metal appliqués originating from unknown archaeological contexts. This practice is even more justified in light of the high percentage of stray finds. Examined from a sourcecritical angle, the registered units were classified into the following categories: 1.) unpublished stray finds: 39 units; 2.) unpublished grave finds: 38 units; 3.) single stray finds: 46 units; 4.) stray finds appertaining to a cemetery: 27 units; 5.) stray finds belonging to grave assemblages/ disturbed graves: 26 units; 6.) undisturbed/fairly intact grave assemblages without sufficient information about the whole cemetery: 33 units; 7.) undisturbed/fairly intact grave assemblages of entirely excavated cemeteries: 38 units. The above brief statistics clearly indicate that some 31.2% of the catalogued units remained unpublished, while further 29.5% represents stray finds lacking a proper original archaeological context. The remaining 39.3% poses further difficulties, too. The 38 units appertaining to entirely or fairly completely excavated cemeteries originate from 21 burial grounds, among which four appear to be single graves, while, on the other hand, only six cemeteries include more than 50 graves. In three cemeteries (Hetény [Chotín, SK], Mözs, Vágtornóc [Trnovec nad Váhom, SK]) among the lattermentioned six, the (belt) mounts were placed in grave in secondary position. Therefore only the three further burial grounds, i.e. the cemeteries excavated at KarosEperjesszög (cemetery no. II), Kiskeszi [Maié Kosihy, SK), and Sárbogárd-Tringer-tanya are adequate for a horizontal stratigraphic analysis. The paper’s second part addresses problems related to the mounts’ manufacturing technology. After macroscopically examining more than 1500 tenthcentury (belt) mounts, the author concludes that, except a unique set produced by using the Pressblech technique, all currently known (belt) mounts produced in the Carpathian Basin were cast using the same technology (i.e., the so-called ‘thin casting’, being a special variant of the cire perdue technique, described by C o a t s w o r t h - P in d e r 2002, 80. and B ü h l e r 2006). This technological uniformity does not provide archaeologists with useful tools for developing a more precise chronological system. On the other hand, mounts of similar shape and design can be compared by projecting their photos of one another or using a 3D scanning technology so as to establish whether certain mounts were manufactured by applying the same master model. This procedure, however, resulted in only partial success. In a number of cases the application of the same master model could be established, but in almost all of these instances one or both units of these ‘pairs’ are stray finds and therefore the chronological consequences of the mounts’ close connection cannot be fully exploited. A further result of the personal investigations was the determination of the approximate width (2-3 cm) and thickness (0.2-0.3 cm) of the majority of tenth-century belts. This fairly narrow and thin leather belt as well as its small mounts only rarely showing well-identifiable signs of wear indicate that these belts were display objects rather than functional ‘weapon belts’ as often assumed in the archaeological literature.
Keywords: Bölcsészettudományok; Történettudomány és régészet